"Love Your Enemies": The Adamic Wisdom of Q 6:27–28, 35c–d. (February 2013) - Joseph, Simon J.
The interpretation of Q 6:27 highlights a perennial problem in biblical scholarship. If Jesus commanded his disciples to love their enemies—and scholars are in virtually unanimous agreement that he did—how are we to understand this imperative in its original Jewish context? How are we to affirm that Jesus criticized his own tradition—which did not encourage love of enemies—without falling into anti-Jewish rhetoric? Our contemporary concern with Jesus' Jewishness should not preclude us from recognizing the possibility that Jesus criticized certain aspects of the Jewish tradition. The purpose of this essay is to isolate a distinctive element of the early Jesus tradition in its original Jewish context, identify its Christological implications, and explore how an intra-Jewish polemic was subsequently transferred onto inter-religious Jewish/Christian relations.